Magneto-thermopower and magnetoresistance of single Co-Ni alloy nanowires - Boehnert, Tim; Vega, Victor; Michel, Ann-Kathrin; Prida, Victor M.; Nielsch, Kornelius (Applied Physics Letters, 2013)
The magneto-thermopower is measured and correlated to the anisotropic magnetoresistance of Co-Ni alloyed nanowires with varying composition. The highest absolute and relative variation of the Seebeck coefficient in perpendicularly applied magnetic fields at room temperature is determined to be 1.5 μVK-1 for Co0.24Ni0.76 and 8.1% for Co0.39Ni0.61 nanowires. Power factors of 3.7 mW/mK 2 have been achieved, which is competitive with common thermoelectric materials like Bi2Te3. For Co-Ni nanowires containing up to 39% Co, a linear relationship between the magnetic field dependent change of the Seebeck coefficient and the electrical conductivity is found. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-20